THE ROLE OF INTERVENTIONAL RADIOLOGY IN POSTOPERATNE COMPLICATIONS OF BILIARY SYSTEM - T. CUMHUR; T. ÖLÇER; A. MAVİŞ and E. ÖZDEMİR and K. ARDA and S. KARAKÖSE and B. ŞAHİN and B. SELÇUK (Turkish Journal of Gastroenterology, 2020)
-